Agama dan Kepribadian dalam Perspektif Psikoanalisis Sigmund Freud - Fitri Nur Ramdaina; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the relationship between religion and personality from the perspective of Sigmund Freud's psychoanalysis. This study uses a qualitative method with a literature study approach. The results of this study indicate that Freud viewed religion as an illusion because it was born from human desires. According to him, religion is just an outlet for disappointment and human escape in the face of conflict, depression, stress, anxiety, and so on. Freud believed that a person's religious behavior is in the subconscious. Religious behavior is solely driven by the desire to avoid a dangerous situation that will befall him and give him a sense of security. For that purpose, humans create a concept that can protect themselves from all these dangers. The concept is summed up in the word